A Review of Studies on Participatory Early Warning Systems (P-EWS): Pathways to Support Citizen Science Initiatives - Marchezini, Victor; Horita, Flávio Eduardo Aoki; Matsuo, Patricia Mie; Trajber, Rachel; Trejo-Rangel, Miguel Angel; Olivato, Débora (Frontiers in Earth Science, 2018)
Context: Global environmental change and disasters pose several challenges to governments, society and science. These challenges occurred in social contexts were information and communication technologies can be used to share data and information, engaging citizen scientists in multidirectional and decentralized knowledge creation initiatives. Often referenced as participatory (or people-centered) early warning systems, this has been of a great potential to improve decisions taken by both emergency institutions and exposed and/or affected communities. Several methodologies have been proposed, mainly in natural science, redefining traditional ways of transferring knowledge about scientific process to the public. Gap: However, practice and research still lack studies that investigate how citizens can be involved in citizen science to support early warning systems. From a social science perspective, this is important as these works do not fill the gap between citizen science and disaster prevention. While, on a technological and perspective, efforts have been concentrated on developing systems, methodologies, and approaches rather than understanding citizens’ requirements or ways of better engaging citizens. Obj: This paper provides a social science framework to determine the elements of how citizen science and participatory early warning systems can be bridged. Method: For doing so, we will conduct a systematic mapping for examining the literature on citizen science and disaster management, in particular, those focused on social science and participatory approaches for early warning systems. Results of this review showed that only 3,35% (14 of 417) articles were related to citizen science and P-EWS, which indeed indicate that much effort is needed to disseminate what is citizen science and how it can be mainstreamed in DRM field. Furthermore, the proposed framework can contribute by enhancing stakeholders’ reflexivity about EWS.